2012
DOI: 10.1542/peds.2011-3755
|View full text |Cite
|
Sign up to set email alerts
|

Local Macroeconomic Trends and Hospital Admissions for Child Abuse, 2000–2009

Abstract: Multicenter hospital data show an increase in pediatric admissions for physical abuse and high-risk TBI during a time of declining all-cause injury rate. Abuse and high-risk TBI admission rates increased in relationship to local mortgage delinquency and foreclosure trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 32 publications
1
82
2
Order By: Relevance
“…This pattern, which is apparent in our raw data and the estimates from our survival analyses, supports findings from prior research linking macro-level foreclosure rates with child maltreatment prevalence. 36,37 An examination of the timing of these events, however, reveals that increased risk of CPS involvement is apparent as much as 12 months before a foreclosure filing, although households continue to be at heightened risk of CPS involvement through the 6 to 12 months after the filing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern, which is apparent in our raw data and the estimates from our survival analyses, supports findings from prior research linking macro-level foreclosure rates with child maltreatment prevalence. 36,37 An examination of the timing of these events, however, reveals that increased risk of CPS involvement is apparent as much as 12 months before a foreclosure filing, although households continue to be at heightened risk of CPS involvement through the 6 to 12 months after the filing.…”
Section: Discussionmentioning
confidence: 99%
“…They found positive associations of mortgage delinquency and foreclosure rates with both types of admissions. 36 Frioux et al estimated associations of county-level unemployment and mortgage foreclosure rates with child maltreatment investigations and substantiations. Their results indicate that both factors are positively associated with CPS investigations and substantiations.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Other studies show that socioeconomic factors measured at a more aggregate ecological level are also associated with maltreatment. 16,29 To our knowledge, our study is the first to specifically examine income inequality as an important risk factor associated with child maltreatment.…”
Section: Figurementioning
confidence: 99%
“…[12][13][14][15] Recently, a retrospective study of children admitted to 38 hospitals between 2000 and 2009 showed that rates of admissions for physical abuse and high-risk traumatic brain injury were significantly related to increases in local mortgage foreclosure and delinquency rates in the associated metropolitan areas. 16 Although there is considerable evidence that income inequality has a negative impact on health and wellbeing for both adults and children, and that poverty is associated with rates of child maltreatment, no study has examined the association of income inequality with child maltreatment. The goal of this study was to examine this association using county-level data on income inequality and corresponding child maltreatment rates in the United States over a 5-year period.…”
mentioning
confidence: 99%
“…most studies use longitudinal data techniques to examine the temporal relationship. For example, Wood et al (2012) show that hospital admissions for child abuse rise the year after an increase in mortgage stress. shows that higher unemployment rates (measured at a state level) are strongly linked to increased substance abuse among US youth, particularly for illicit drug use.…”
mentioning
confidence: 99%